Enhanced recovery in patients with gestational diabetes mellitus and MTHFR 677 TT genotype after taking high-dose folic acid supplements during mid-late pregnancy: an open-label interventional study - Ying, Jun; Zhang, Jie; Li, Piyu; Liu, Lu; Li, Yan; Lau, Winnie W.Y.; Chu, Qiao; Wu, Benqing; Wang, Xiaonan; Zhang, Hui (Frontiers in Endocrinology, 2023)
Objective To explore the relationship between folic acid supplementation and the recovery rate of gestational diabetes mellitus (GDM) in women with methylenetetrahydrofolate (MTHFR) 677 TT genotypes in mid-late pregnancy. Methods 9, 096 pregnant women were recruited with their MTHFR gene genotyped. 5,111 women underwent a 75-g oral glucose tolerance test (OGTT) and 2,097 were confirmed with GDM. The association between MTHFR genotypes and GDM risk was estimated using logistic and log-binomial regression, with age and parity set as the covariates to control their confounding effects. Further assessment of GDM risk on glucose levels was done using the ACONVA model. As an open-label intervention study, 53 GDM patients with TT genotype were prescribed 800μg/day of folic acid as the high-dose group, while 201 GDM patients were given 400μg/day as the standard-dose group at their 24-28 weeks of pregnancy. A rate ratio (RR) of GDM recovery was estimated at each available time point for both groups. The time-to-GDM persistence events were analyzed with the Kaplan-Meier method and Cox-regression model. The trend of glucose levels over time was estimated using the linear model. Results MTHFR 677 TT genotype has no significant association with the glucose levels and GDM risk, with an adjusted OR of 1.105 (95% CI 0.853, 1.431; p=0.452) and an adjusted PR of 1.050 (95% CI 0.906, 1.216; p=0.518) compared to the wildtype CC group. Patients in the high-dose group (n=38; 15 drop-outs; 40.69 days (95% CI 33.22, 48.15)) recovered from GDM approximately 27 days faster than those in the standard-dose group (n=133; 68 drop-outs; 68.09 days (95% CI 63.08, 73.11)). Concomitantly, the RR of GDM recovery rose and reached 1.247 (95% CI 1.026, 1.515) at 100 days of treatment with the standard-dose group as reference. Conclusions High-dose folic acid supplement intake in mid-late pregnancy is associated with faster GDM relief in patients with MTHFR 677 TT genotype compared to the standard dose, which would be served as a novel and low-cost alternative therapy for the treatment of GDM.